ADAPTATION OF BUSINESS STRATEGIES AMONG AGRI-FOOD MICRO-ENTERPRISE: IMPACT OF COVID-19 PANDEMIC - Zuliana Zakaria; Nur Badriyah Kamarul Zaman; Nur Maizatul Idayu Othman; Nur Nabila Huda Aziz (International Journal of Accounting, Finance and Business, 2022)
As the Covid-19 outbreak continues to spread across the world, it is essential to address its existing and potential impacts on the agri-food sector, from the perspective of micro-entrepreneurs. Undeniably, the impact of pandemic outbreak is more significant among micro-entrepreneurs compared to macro-entrepreneurs. In Malaysia, almost 90% of agri-food establishments are small and medium enterprises (SMEs). Movement Control Order (MCO) affected the existing business model of agri-food micro-entrepreneurs. Existing business models are no longer relevant to adapt with the new norm. As the consequences, among the hurdles SMEs have to face are closure of business operation, laying off workers, and cash flow issue. Therefore, it is crucial to explore the strategies taken by micro-entrepreneurs in dealing with the crisis and how these measures affect the change of business model. This is exploratory types of study that involves unstructured phone interviews using open ended questions with micro-entrepreneurs that offering agri-food product. The result from unstructured interview with two agri-food micro-entrepreneurs in Klang Valley, Selangor provide perspective on the business strategy restructuring during Covid-19 and modification on the business model as the initiative to recover after the crisis. This study will significantly contribute to the agri-food micro-entrepreneurs as a reference on the survival strategy during and after the pandemic.